Clonality of multifocal nonsmall cell lung cancer: implications for staging and therapy - Warth, Arne; Macher-Göppinger, Stephan; Muley, Thomas; Thomas, Michael; Hoffmann, Hans; Schnabel, Philipp Albert; Penzel, Roland; Schirmacher, Peter; Aulmann, Sebastian (The European respiratory journal, 2012)
Nonsmall cell lung cancers (NSCLCs) display a variety of morphological and molecular features. Accurate subtyping of NSCLC has been shown to predict patient survival as well as response rates and toxicities of specific drugs. Assessment of multifocal lung tumours and the distinction of synchronous primary tumours from intrapulmonary metastases represent an important problem as this decision significantly influences tumour staging and subsequent treatment strategies. In order to provide a basis for evidence-based treatment decisions in these patients, we analysed the clonal relationship of multifocal NSCLC with indistinguishable histomorphology in a series of 78 patients by allelotyping (using polymorphic short tandem repeat markers) as well as KRAS and epidermal growth factor receptor (EGFR) mutation testing. Our data demonstrate a common clonal origin indicative of intrapulmonary metastases in almost two-thirds (∼62%) of the cases, while ∼36% of multifocal NSCLC displayed unique molecular profiles suggesting separate primary tumours. Divergent KRAS and/or EGFR mutations were observed in ∼8% of all cases. With the increased availability of EGFR-targeted therapy options, nonresectable, multifocal NSCLC with diverging KRAS and/or EGFR mutations are likely to show different treatment responses, underlining the need to separately analyse multifocal tumours. Obviously, this also holds true for further, novel molecular predictors of targeted therapies.
First published online: 10 October 2011
Gesehen am 11.10.2018